Hermenéutica crítica en la práctica del trabajo social - Cordero Ramos, Nuria; Fernández Martín, María Isabel; Palacios Esteban, José Emilio (Acciones e Investigaciones Sociales, 2011)
Hermenéutica crítica en la práctica del trabajo social